Determining Competence in Performing Obstetric Combined Spinal-epidural Procedures in Junior Anesthesiology Residents: Results From a Cumulative Sum Analysis. Issue 3 (September 2021) - Lew, E.; Allen, J.C.; Goy, R.W.L.; Ithnin, F.; Sng, B.L.
Abstract : ( Int J Obstet Anesth . 2020;44:33–39) Epidural techniques can be challenging to master and require practice. The required number of cases to demonstrate competency in epidural procedures varies widely. Residents must complete 40 epidural or combined spinal-epidurals (CSEs) to show competency according to Accreditation Council for Graduate Medical Education International (ACGME-I) requirements. At the study center, CSE training consists of didactic teaching, 10 one-on-one supervised sessions using a model, and 10 supervised and coached CSEs, followed by 3 Direct Observation of Procedures assessments. This study used cumulative sum (CUSUM) analysis, a tool for defining failure rates, plotting learning curves and mapping levels of competence, to determine the minimum experience needed to demonstrate competency in obstetric CSE procedures among junior residents.